KONSEP PENCIPTAAN ALAM (MAKHLUK): PEMBUKTIAN PENCIPTAAN DAN TANGGUNG JAWAB - Hafizon, Ahmad; Hitami, Munzir; Yusuf, Kadar M (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
The creation of nature is proof of the power and greatness of Allah SWT. This fact proves the vastness of Allah's knowledge compared to the knowledge we have. There is no difficulty for Allah to create as well as destroy this universe. This expression of gratitude for all the blessings of the universe is evidenced by a better friendly attitude towards nature. The cosmological verses in the Qur'an are another sign of the fact of the universe. Both explain each other